да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайтответ:
да х_р тебе в рот личинка
Объяснение:
п_дуй от сюда н_уй это го*но-сайт
Объяснение:
G(x)= (x-3)(x^2+4x+4)
G(x)= x^3+4x^2+4x-3x^2-12x-12
G(x)= x^3+x^2-8x-12
g’(x)= 3x^2+2x-8
3x^2+2x-8<0
D= 4+96=100
x1= (-2-10)/6= -2
x2= (-2+10)/6= 4/3
(x+2)(x-4/3)<0
x€(-2;4/3)